IBM HiperSockets implementation guide - Ebbers, Mike (IBM Corp., International Technical Support Organization, 2014)
"This IBM Redbooks publication provides information about the IBM System z HiperSockets function. It offers a broad description of the architecture, functions, and operating systems support. This publication will help you plan and implement HiperSockets. It provides information about the definitions needed to configure HiperSockets for the supported operating systems. This book is intended for system programmers, network planners, and systems engineers who want to plan and install HiperSockets. A solid background in network and Transmission Control Protocol/Internet Protocol (TCP/IP) is assumed."--
Includes bibliographical references. - Online resource; title from cover (Safari, viewed July 24, 2014)
Keywords: TCP/IP (Computer network protocol); Web servers; IBM computers -- Programming; TCP/IP (Protocole de réseaux d'ordinateurs); Serveurs Web; IBM (Ordinateurs); Programmation; IBM computers; Programming; Electrical & Computer Engineering; Engineering & Applied Sciences; Telecommunications